2020
DOI: 10.1104/pp.20.00348
|View full text |Cite
|
Sign up to set email alerts
|

Citrus CsACD2 Is a Target of Candidatus Liberibacter Asiaticus in Huanglongbing Disease

Abstract: Citrus Huanglongbing (HLB), caused by Candidatus Liberibacter asiaticus (Las), is one of the most destructive citrus diseases worldwide, yet how Las causes HLB is poorly understood. Here we show that a Las-secreted protein, SDE15 (CLIBASIA_04025), suppresses plant immunity and promotes Las multiplication. Transgenic expression of SDE15 in Duncan grapefruit (Citrus 3 paradisi) suppresses the hypersensitive response induced by Xanthomonas citri ssp. citri (Xcc) and reduces the expression of immunity-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 51 publications
1
65
0
1
Order By: Relevance
“… Gene details Identified/cloned Function study Target trait Reference 1 Papain-like cysteine protease Sweet orange Citrus Huanglongbing Clark et al. (2018) 2 Accelerated cell death 2 Sweet orange Duncan grapefruit Pang et al. (2020) 3 2-oxoglutarate and Fe(II)-dependent oxygenase gene US-897 ( Citrus reticulata × Poncirus trifoliata ) Albrecht and Bowman (2011) 5 PtCDR2 and PtCDR8 P. trifoliata Rawat et al.…”
Section: Key Genes Associated With Citrus Domestication and Their Impmentioning
confidence: 99%
“… Gene details Identified/cloned Function study Target trait Reference 1 Papain-like cysteine protease Sweet orange Citrus Huanglongbing Clark et al. (2018) 2 Accelerated cell death 2 Sweet orange Duncan grapefruit Pang et al. (2020) 3 2-oxoglutarate and Fe(II)-dependent oxygenase gene US-897 ( Citrus reticulata × Poncirus trifoliata ) Albrecht and Bowman (2011) 5 PtCDR2 and PtCDR8 P. trifoliata Rawat et al.…”
Section: Key Genes Associated With Citrus Domestication and Their Impmentioning
confidence: 99%
“…The N-terminal GFP-tagged m4405 was detected under confocal fluorescence microscopy. As shown in Figure 3B, m4405-GFP was predominately colocalized with the plasma membranal marker pm-rk CD3-1007 (Nelson et al, 2007), indicating the plasma membrane localization of m4405 in plants. Using the same strategy, we observed that CLIBASIA_04405 shared a similar subcellular localization in N. benthamiana cells with m4405 ( Figure 3B).…”
Section: Benthamiana Cellsmentioning
confidence: 75%
“…In contrast, the pathogens, including bacteria, fungi, oomycetes, and nematodes, often secrete an arsenal of effectors that contribute to cell death suppression to enable their successful infection (da Cunha et al, 2007;Dou and Zhou, 2012;Goverse and Smant, 2014;Lo Presti et al, 2015). In CLas, the mature forms of two Sec-dependent secretory proteins CLIBASIA_03875 and CLIBASIA_04025, termed m3875 and SDE15, have been determined as PCD suppressors (Zhang et al, 2019;Pang et al, 2020). Herein, we demonstrated that m4405, the mature form of the Sec-dependent secretory protein CLIBASIA_04405, also inhibited hypersensitive cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations